Permasalahan Hukum Usaha Neynis Food Ditinjau Dari Peraturan Menteri Perdagangan Nomor 71 Tahun 2019 Tentang Penyelenggaraan Waralaba - Nicholas Firman Rafael Napitupulu; Raden Muhammad Fadly Latief Ashshiddiq Prawirawinata; Nyulistiowati Suryanti; Deviana Yuanitasari (Jurnal Relasi Publik, 2024)
Franchising is a business system carried out by two parties, namely the Franchisor and the Franchisee, in which the Franchisor grants license rights to the Franchisee based on the Agreement. This Franchise Agreement is a legal basis that is made in writing. In order for a business to be said to be a franchise, it must follow the criteria specified in the regulations, one of which is registering the prospectus of the franchise agreement and ownership of the Franchise Registration Certificate. However, in reality, in this case Neynis Food, has not registered its business with the state, but has claimed itself as a business that opens a franchise. Therefore, the author conducts research to obtain an overview of the legal consequences that occur if the Franchisor does not register its franchise and legal protection for Franchisees. This paper is made using the normative juridical research method. This research is conducted by investigating secondary data, which means that this research examines the laws that apply to society and their implementation in practice. The results of the research on this issue show how the implementation of Indonesian laws and regulations on franchising practices in Indonesia and it is known that the Neynis Food business cannot be qualified as a franchise, and if it continues to claim itself as a franchise, then the business can be said to be illegal because it does not fulfill the elements of franchising regulated in Permendag 71 of 2019.